Employability skills and core self-evaluations as predictors of perceived employability among undergraduate students of a Nigerian University - Aigbodion, Andrew I.; Uye, Emmanuel E.; Timeyin, Adams (ESUT JOURNAL OF SOCIAL SCIENCES, 2022)
This study investigated employability skills and core self-evaluations as predictors of perceived employability among undergraduate students of Ambrose Alli University, Nigeria. A cross-sectional survey design was adopted while stratified random sampling technique was used to select 300 undergraduate students for the study. Three instruments: Perceived Employability Scale, Employability Skills Scale, and Core Self-evaluations Scale were used for data collection while standard multiple regression analysis was used to test the three stated hypotheses. The results revealed that employability skills and core self-evaluations jointly predicted perceived graduate employability (R = .556, R2= .310, F = 66.570, P < .05). Also, employability skills independently predicted perceived graduate employability (β = .482, t = 11.288, P < .05). However, core self-evaluations did not independently predict perceived graduate employability (β = .077, t = 1.091, P >.05). The study concluded that employability skills and core self-evaluations are good predictors of perceived graduate employability. It is recommended that skill acquisitions should be mandated as one of the requirements for students to graduate from any higher institution of learning to enhance their employability confidence.